Management of Oil Wealth Under the Permanent Income Hypothesis : The Case of Sao Tome and Principe - Segura Vasi, Alonso (Washington, D.C. : International Monetary Fund, 2006)
This paper documents the protracted process of shaping the rules governing oil operations in Sao Tome and Principe. It analyzes the institutional framework for oil sector development, which applies Milton Friedman's permanent income hypothesis to the management of oil resources. Sao Tome and Principe is the first country in Africa to adopt this rule. Finally, the paper offers a preliminary quantitative analysis of the impact of oil sector development on government consumption and savings. It shows that the country's oil wealth could be significant, which would enable sustainable government consumption and intergenerational equity through a gradual buildup of the Permanent Fund for Future Generations.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet